2011
DOI: 10.1016/j.febslet.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

PANDER KO mice on high-fat diet are glucose intolerant yet resistant to fasting hyperglycemia and hyperinsulinemia

Abstract: The recent creation of the PANDER knockout (PANKO) and acute mouse models have revealed a biological function in the regulation of glycemic levels via promotion of hepatic glucose production (HGP) and pancreatic β-cell insulin secretion. Therefore, we hypothesized that the absence of PANDER may afford some degree of protection from high-fat diet (HFD) induced fasting hyperglycemia. On HFD, fasting glycemic levels were significantly lower in the PANKO mice. Also, fasting insulin levels and the in-vivo insulin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Wilson et al . also reported that circulating PANDER is elevated in obese C57BL/6 mice . The relationship between PANDER and insulin in β cells may be similar to that between amylin (islet amyloid polypeptide, a 37‐amino acid peptide) and insulin.…”
Section: Fam3b (Pander) and Nafldmentioning
confidence: 80%
See 3 more Smart Citations
“…Wilson et al . also reported that circulating PANDER is elevated in obese C57BL/6 mice . The relationship between PANDER and insulin in β cells may be similar to that between amylin (islet amyloid polypeptide, a 37‐amino acid peptide) and insulin.…”
Section: Fam3b (Pander) and Nafldmentioning
confidence: 80%
“…Immunohistochemical staining and confocal microscopy assays further revealed that FAM3B protein is specifically localized in the islets within the pancreas . Therefore, FAM3B is also called PANDER in subsequent studies . Human and mouse PANDER proteins are composed of 235 amino acid residues with a 29‐amino acid N‐terminal signal peptide and share high‐sequence homology among species.…”
Section: Fam3b (Pander) and Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, while there were no differences in fasted glucose levels in the PANKO mice on normal chow diet, after HFD feeding for 10 weeks, glucose levels following a 24-or 48-h fast were significantly lower in PANKO mice [17,22] and more similar to their normal diet (ND, 16.7% fat by calories) fed counterparts. This suggests that loss of PANDER may protect mice on a HFD from developing gross fasting hyperglycemia and that PANDER may be an important target for inhibiting HFD-induced fasting hyperglycemia.…”
Section: Pander Lipids and Hyperglycemiamentioning
confidence: 89%